Mahremî of Tatavla, a sixteenth-century Divan poet, and his Şütür-nâme - Demirel, Şener (My University, 2005)
WThe story tradition of Turkish literature has quite a long history. In Classical Turkish literature, stories were mostly written in verse, using the mesnevi pattern, but occasionally some artists used prose. One of the works written in prose is the Şütür-nâme by Mahremi, a 16 th-century poet. This article contains a transliteration and study of this work. Şütür-nâme is a work in which the adventures of an old person named Father Şütür are recounted in an allegorical way. The work is used to convey certain massages to the reader via the person of Father Şütür. Persian poems scattered among the stories in the text and especially similes and idioms about the camel are used in strikingly appropriate places. Besides, when we evaluate the language and style we can state that Şütür- nâme is one of the good examples of simple prose.
16. Yüzyil Di?van şai?rleri?nden Tatavlali Mahremî ve Şütür-nâmesi?
Keywords: Mahremi; Şütür-nâme; Story